Investigation of the relationship between community-acquired respiratory distress syndrome toxin and the high-mobility group box protein 1-toll-like receptors-myeloid differentiation factor 88 signaling pathway in Mycoplasma pneumoniae pneumonia - Yujie Fan; Ying Ding; Yuqin Li; Dandan Zhang; Min Yu; Wei-fang Zhou; Xiaoxing Kong (BMC, 2022)
Abstract Background In recent years, reports of refractory Mycoplasma pneumoniae pneumonia (RMPP) have gradually increased, including reports on how these conditions threaten the lives of children. However, the specific mechanism of Mycoplasma pneumoniae pneumonia (MPP) remains unclear. This study aimed to investigate the relationship between community-acquired respiratory distress syndrome toxin (CARDS TX) and High-mobility group box protein 1-Toll-like receptors-Myeloid differentiation factor 88 (HMGB1-TLRs-MyD88) in MPP and to examine the immune pathogenesis of Mycoplasma pneumoniae infection. Methods Children who were diagnosed with MPP and examined by bronchoscopy were included in the MPP group. Additionally, children who underwent bronchoscopy because of bronchial foreign bodies in the same period were included in the control group. Gene expression of CARDS TX, HMGB1, Toll-like receptor 2 (TLR2), Toll-like receptor 4 (TLR4), MyD88, and cluster of differentiation 14 (CD14) in bronchoalveolar lavage fluid (BALF) were detected using real-time reverse transcription-polymerase chain reaction. Correlations between CARDS TX and HMGB1-TLRs-MyD88 were analyzed. Results CARDS TX, HMGB1, TLR2, MyD88, and CD14 mRNA expression in BALF in the MPP group was significantly higher than that in the control group (all P < 0.05). CARDS TX mRNA expression was positively correlated with HMGB1, TLR2, MyD88, and CD14 mRNA expression (all P < 0.05). Furthermore, HMGB1 mRNA expression was positively correlated with TLR2, MyD88, and CD14 mRNA expression (all P < 0.05). Conclusions CARDS TX may participate in the immune pathogenesis of MPP through the HMGB1-TLRs/CD14-MyD88 pathway.